2024
DOI: 10.1037/vio0000506
|View full text |Cite
|
Sign up to set email alerts
|

“One by one, they raped me”: Sexual violence against khwaja sira in Swat, Pakistan.

Sameena Azhar,
Imtyaz Ahmad,
Nadeem Tariq

Abstract: Objective: The objective of the present study was to explore themes related to sexual violence against khwaja sira in Mingora, Swat, Khyber Pakhtunkhwa, Pakistan. Method: We conducted 45 in-depth interviews with khwaja sira in Mingora, Swat on their lived experiences with sexual violence. Interviews were digitally audio recorded in Pashto, then translated into English for coding, interpretation, and thematic content analysis of the transcripts. Results: We identified the following themes regarding sexual viole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Abuse involving third gender individuals often remain undocumented and unaddressed (Fatima et al, 2022 ). Khwaja sira in Khyber Pakhtunkhwa, Pakistan have faced social exclusion and limited opportunities throughout their lives, including family and social rejection (Azhar et al 2023 ; Azhar, Ahmad and Tariq, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abuse involving third gender individuals often remain undocumented and unaddressed (Fatima et al, 2022 ). Khwaja sira in Khyber Pakhtunkhwa, Pakistan have faced social exclusion and limited opportunities throughout their lives, including family and social rejection (Azhar et al 2023 ; Azhar, Ahmad and Tariq, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, many participants reported that their family members distanced themselves in order to protect themselves from public shame or dishonor (Alizai, Ahmad and Tariq, 2017 ). Khwaja sira have also endured recurring sexual violence, often starting in childhood and persisting into adulthood (Azhar, Ahmad and Tariq, 2024 ). In Mingora, KP, khwaja sira have experienced significant physical and sexual violence, including kidnapping, robberies, beatings, and multiple gang rapes (Azhar et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%